2021
DOI: 10.21037/atm-20-1793a
|View full text |Cite
|
Sign up to set email alerts
|

Supercapsular percutaneously-assisted total hip (SuperPath) versus mini-incision posterolateral total hip arthroplasty for hip osteoarthritis: a prospective randomized controlled trial

Abstract: Background: Supercapsular percutaneously-assisted total hip (SuperPath) arthroplasty has been proposed to be minimally invasive and tissue sparing, with possible superior postoperative outcomes compared with conventional approaches for total hip arthroplasty (THA). However, previous studies have underlined the shortcomings of conventional THA approaches, including higher dislocation, more blood loss, longer incisions, more tissue damage, and delayed postoperative rehabilitation. In the present study, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 49 publications
0
58
1
Order By: Relevance
“…One of the advantages of minimally invasive surgery is that it can reduce the muscle and soft tissue impairment.In previous studies, SuperPATH approaches are correlated with lower levels of in ammation markers comparing with standard approaches [12].However,a recent study demonstrated that the SuperPATH group unexpectedly yielded more soft tissue damage and signi cantly increased serum CK levels compared with the PLA group on day 3 postoperatively [13].In our study, no difference was found concerning the increase of serum CRP,CK and ESR levels between the two groups.These inconsistent results are possibly attributable to additional intraoperative soft tissue (mainly muscle) damage from many sources , including intraoperative stretching , unintentional detachment , and varied instrument retraction , during the signi cantly elongated time taken to perform the procedure.A cadaveric model study by Amanatullah et al showed that the piriformis-sparing posterior approach to the hip causes inadvertent damage to the piriformis muscle in >90% of cases and that this damage occurs outside of the surgical eld [14].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…One of the advantages of minimally invasive surgery is that it can reduce the muscle and soft tissue impairment.In previous studies, SuperPATH approaches are correlated with lower levels of in ammation markers comparing with standard approaches [12].However,a recent study demonstrated that the SuperPATH group unexpectedly yielded more soft tissue damage and signi cantly increased serum CK levels compared with the PLA group on day 3 postoperatively [13].In our study, no difference was found concerning the increase of serum CRP,CK and ESR levels between the two groups.These inconsistent results are possibly attributable to additional intraoperative soft tissue (mainly muscle) damage from many sources , including intraoperative stretching , unintentional detachment , and varied instrument retraction , during the signi cantly elongated time taken to perform the procedure.A cadaveric model study by Amanatullah et al showed that the piriformis-sparing posterior approach to the hip causes inadvertent damage to the piriformis muscle in >90% of cases and that this damage occurs outside of the surgical eld [14].…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies had con rmed that the VAS score were lower and HS was higher in the SuperPATH cohort comparing to the conventional approach in the early operative phase [20].Our study also con rmed the same results.However,the meta-analysis by Ramadanov found that no differences in pain VAS between hip replacements via SuperPATH and conventional approaches 1, 3 days, 3 and 12 months postoperatively [7].On the contrary,Meng et al [13] found that pain VAS was signi cantly higher in the SuperPath group (7.05) compared with the PLA group (6.55) on postoperative day 3 and remained comparable between both groups at other time points within 1 year postoperatively.The meta-analysis by Ramadanov reported that HS on 7 days postoperatively was 10.2 higher in hip replacement via SuperPATH approach compared to hip replacement via conventional approaches [7]. Meng et al [13] reported that differences in average HHS were not signi cant between the PLA groups and SuperPath groups at any time point,hip function was observed to be signi cantly improved on postoperative day 14 (70.66±6.22) in the PLA group, but only showed a signi cant improvement at 3 months postoperatively (82.44±3.51) in the SuperPath group. Their data indicated that SuperPAHT was associated with overall inferior patient-reported outcomes during the early postoperative phase in terms of pain symptoms and hip function.…”
Section: Discussionmentioning
confidence: 96%
“…Controversies exist over the precise definition of a minimally invasive approach, as no clear definition is reported [ 22 , 41 , 48 ]. The SuperPath technique fits into the group of minimally invasive muscle-sparing techniques, since it preserves the cutting of the extrarotator muscles, hip joint capsule, and avoids surgical dislocation of the femoral head [ 46 ]. Several studies report benefits related to this technique [ 22 , 23 , 47 , 49 – 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Controversies exist over the precise de nition of a minimally invasive approach, as no clear de nition is reported [22,37,45]. The SuperPath technique ts into the group of minimally invasive muscle-sparing techniques, since it preserves the cutting of the extrarotator muscles, hip joint capsule, and avoids surgical dislocation of the femoral head [43]. Several studies report bene ts related to this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated acetabular cup placement depending on the surgical approach [29,[39][40][41]. MIS techniques arose with the simultaneous effort to reduce periarticular tissue damage and achieve good clinicalradiographic results, the latter at least overlapping with those obtained with traditional surgical approaches [42][43][44]. In this regard, it would also be appropriate to clarify the correct de nition of MIS, since the surgical approaches are manifold and different from each other.…”
Section: Discussionmentioning
confidence: 99%